2011
DOI: 10.1007/s11230-011-9303-1
|View full text |Cite
|
Sign up to set email alerts
|

Putting in shape – towards a unified approach for the taxonomic description of monogenean haptoral hard parts

Abstract: Among monogeneans, haptoral hard parts provide prominent morphological characters upon which identifications are largely based. Traditionally, morphometric approaches are based on the use of arbitrary collections of linear distance measurements between landmarks. An exhaustive review of the specific diagnoses published in the journal Systematic Parasitology highlights the fact that an intricately important number of measurements are used to describe the same morphological features. Hence, this does not allow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Morphological species identification is usually based on only a few characters and is far from straightforward as it requires sophisticated morphometric techniques [57]. Molecular species identification in Gyrodactylus was therefore highly welcomed, and currently relies largely on sequencing of the ribosomal internal transcribed spacers (ITS).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological species identification is usually based on only a few characters and is far from straightforward as it requires sophisticated morphometric techniques [57]. Molecular species identification in Gyrodactylus was therefore highly welcomed, and currently relies largely on sequencing of the ribosomal internal transcribed spacers (ITS).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that multiple authors (Upeniece, 2001(Upeniece, , 2011Littlewood and Donovan, 2003) have suggested that the Middle Devonian hook circlets might belong to a platyzoan helminth, a putative reinvestigation of these fossils could be used to constrain the evolutionary history of this entire group. Many studies on extant flatworms have focused on the hook elements of particular groups (Vignon and Sasal, 2010;Vignon, 2011) or taxa (Shinn et al, 2003). Information and illustrations of these helminth structures can also be found in comprehensive systematic treatments: Yamaguti (1959), Schmidt (1986) and Khalil et al (1994) for Cestoda; Yamaguti (1963a) for Monogenea and Yamaguti (1963b) and Golvan (1969) for Acanthocephala.…”
Section: Free-living Flatwormsmentioning
confidence: 99%
“…In particular, the haptoral attachment organ is characterized by sclerotized structures such as anchors, bars, hooks, etc. The morphology of these organs are usually unique to monogenean species [5] and are used as diagnostic characters in taxonomy [6, 7]. …”
Section: Introductionmentioning
confidence: 99%